Plasma creatine concentration is associated with incident hypertension in a cohort enriched for the presence of high urinary albumin concentration: the Prevention of Renal and Vascular Endstage Disease study. Issue 2 (9th February 2022) - Post, Adrian; Kremer, Daan; Swarte, J. Casper; Sokooti, Sara; Vogelpohl, Fabian A.; Groothof, Dion; Kema, Ido.P.; Garcia, Erwin; Connelly, Margery A.; Wallimann, Theo; Dullaart, Robin P.F.; Franssen, Casper F.M.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: : Hypertension is a major risk factor for cardiovascular disease, kidney disease, and premature death. Increased levels of creatine kinase are associated with development of hypertension. However, it is unknown if creatine, a substrate of CK, is associated with the development of hypertension. We therefore, aimed to investigate the association between plasma creatine concentration and incident hypertension. Methods: We measured fasting plasma creatine concentrations by nuclear magnetic resonance spectroscopy in participants of the population-based PREVEND study. The study outcome was incident hypertension, defined as either a SBP of at least 140 mmHg, a DBP of at least 90 mmHg, or the new usage of antihypertensive drugs. Participants with hypertension at baseline were excluded. Results: We included 3135 participants (46% men) aged 49 ± 10 years. Mean plasma creatine concentrations were 36.2 ± 17.5 μmol/l, with higher concentrations in women than in men (42.2 ± 17.6 versus 29.2 ± 17.6 μmol/l; P < 0.001). During a median of 7.1 [interquartile range: 3.6–7.6] years of follow-up, 927 participants developed incident hypertension. Higher plasma creatine concentrations were associated with an increased risk of incident hypertension [HR per doubling of plasma creatine: 1.21 (95% confidence interval: 1.10–1.34); P < 0.001], which remained significant after adjustment for potential confounders. Sex-stratified analyses demonstrated higher plasma creatine that was independently associated with an increased risk of incident hypertension in men [hazard ratio: 1.26 (95% CI 1.11–1.44); P < 0.001], but not in women (hazard ratio: 1.13 (95% CI 0.96–1.33); P = 0.14]. Causal pathway analyses demonstrate that the association was not explained by sodium or protein intake. Conclusion: Higher plasma creatine is associated with an increased risk of hypertension in men. Future studies are warranted to determine the underlying mechanisms.